Characterization of Lactobacillus spp. isolated from layer hens as probiotic candidates - Jiawei Zhang; Andrea R. McWhorter; Samiullah Khan; Nicky-Lee Willson; Kapil K. Chousalkar (BMC Veterinary Research)
Abstract Background Egg production and performance in commercial layer flocks can be impacted by gastrointestinal health. Probiotics are considered potential alternatives to antibiotics in poultry, and have been proven to have positive impacts on gut health. The objective of this study was to isolate and characterise Lactobacillus strains isolated from high production layer flocks for probiotic properties. Results Eleven different Lactobacillus (L.) species were isolated from faecal samples collected from layer hens in late lay. Species included L. agilis, L. crispatus, L. gallinarum, L. ingluviei, L. johnsonii, L. kitasatonis, L. mucosae, L. oris, L. reuteri, L. saerimneri and L. salivarius. Enterococcus cecorum and Enterococcus faecium as well as Streptococcus alactolyticus were also isolated. Phenotypic properties of the eleven Lactobacillus species were then evaluated to assess their probiotic potential. Bacterial culturability at low pH, under high concentrations of bile salt and sodium chloride, as well as in simulated gastric juice were characterised for each species. Auto- and co-aggregation capacity, adhesion to the intestinal epithelium as well as inhibition of Salmonella Typhimurium were also evaluated. All the Lactobacillus spp. exhibited high culturability in sodium chloride at different temperatures, and exhibited strong adhesion to chicken epithelial cells. L. reuteri, L. salivarius, L. saerimneri, and L. mucosae displayed higher culturability in low pH conditions, and L. johnsonii displayed higher culturability in high concentration of bile salt. Only L. crispatus was culturable in simulated gastric juice after 24 h incubation. L. kitasatonis exhibited strong auto-aggregation and co-aggregation with wild-type Salmonella Typhimurium. All Lactobacillus species exhibited strong inhibition activity against Salmonella Typhimurium. Conclusions The Lactobacillus species isolated in this study exhibited probiotic properties. Further in vivo experiments are required to evaluate their capacity to colonise and persist in the host as well as evaluate their potential effects on the gut microbiota and overall health parameters of layer hens.